K Kadar 17β-estradiol, Vitellogenin, dan Diameter Telur Selama Siklus Reproduksi Oreochromis niloticus - Mainassy, Meillisa Carlen; Manalu, Wasmen; Andriyanto, Andriyanto; Sudrajat, Agus Oman; Kapelle, Imanuel Berly D.; Gunadi, Bambang (IPB University, 2025)
Estradiol, vitellogenin levels, and egg diameter are indicators of oocyte quality in aquaculture. This study evaluated the performance of 17β-estradiol (E2) and vitellogenin (Vtg) concentrations in eggs and oocyte diameter during the reproductive period of Oreochromis niloticus at the Fish Breeding Research Center, Sukamandi, Subang, West Java. Sixmonth- old female fish were fed a diet supplemented with varying doses of curcumin analog in the morning and evening for six weeks. The study used a completely randomized design with seven treatments and three replicates. E2 and Vtg concentrations in eggs were analyzed using the enzyme-linked immunosorbent assay (ELISA) Fish kit. The results indicated that the supplementation of curcumin analog in female broodfish of red tilapia increased the concentration of E2, which in turn stimulated Vtg synthesis in the liver, subsequently stored in developing follicles during gonadal maturation. The group supplemented with 2.4 mg of curcumin analog per 100 g of feed exhibited the highest concentrations of E2 (114.46 ng/mL) and egg Vtg (55.63 mg/mL). This study provides valuable insights for enhancing reproductive performance by incorporating curcumin analogs into the feed for commercial tilapia farming.